Interaction 1 - Baker, Linda R. (The McGraw-Hil Companies, 2003)
Thix book provides an in-depth coverage of the four major language skills: reading, writing, listening, and speaking. In addition, a strong grammar component acts as a foundation for students to rely on while mastering their new skills.